Light and obscurity in symbolism - Neginsky, Rosina; Cibelli, Deborah (Cambridge Scholars Publishing, 2016)
The idea of light and darkness is one of the central ideas of the Symbolist movement, since this is a movement of contrasts. It encompasses the major themes of Symbolism, such as good and evil, beauty and ugliness, the visible and the invisible, and the divine and the earthly. This volume brings together a range of studies in order to understand the notion of light and darkness and a variety of its Symbolist interpretations. It also stresses the interdisciplinary nature of the concepts of light and darkness in Symbolism, as well as the cohabitation and symbiosis of both, which are together or.